Blood-Modified Carbapenem Inactivation Method: a Phenotypic Method for Detecting Carbapenemase-Producing Enterobacteriaceae Directly from Positive Blood Culture Broths - Sfeir, M. M. (J Clin Microbiol, 2020)
A variant of the modified carbapenem inactivation method (mCIM) was developed to detect carbapenemase activity directly from positive blood culture broths. The method, termed “Blood-mCIM,” was evaluated using Bactec blood culture bottles (Becton, Dickinson and Company, Franklin Lakes, NJ) inoculated with 27 different carbapenemase-producing Enterobacteriaceae (CPE) isolates and 34 different non-CPE isolates. The assay was positive for all blood culture broths inoculated with CPE isolates and negative for all blood culture broths inoculated with non-CPE isolates, corresponding to a diagnostic sensitivity and specificity of 100%, respectively. This assay is inexpensive using “off the shelf” reagents, does not require centrifugation or mechanical lysis, and can be readily implemented in any clinical microbiology laboratory. The Blood-mCIM should facilitate expedient administration of antimicrobial therapy targeted toward CPE bloodstream infections and assist infection control and public health surveillance.